Psychological Capital and Perceived Stress in Nurses: The Mediating Role of Need for Recovery and Recovery Experiences - Marie Charlotte Mollet; Oulmann Zerhouni; Arnaud Villieux; Corinne Isnard Bagnis; Lucia Romo (Nursing Open, 2026)
ABSTRACT Aim To examine whether recovery experiences and need for recovery mediate the association between psychological capital and perceived stress in nurses. Design Cross‐sectional online survey. Methods A total of 184 nurses currently practicing in France completed an anonymous online questionnaire administered in January 2023. Participants completed the French versions of the Psychological Capital Questionnaire, the Recovery Experience Scale, the Need for Recovery Scale, and the Perceived Stress Scale. Two mediation models were estimated using ordinary least squares regression with percentile bootstrap inference for the indirect effects. Results Psychological capital was positively associated with recovery experiences and negatively associated with need for recovery. Need for recovery was strongly and positively associated with perceived stress, while psychological capital showed no direct association with perceived stress. The indirect effect of psychological capital on perceived stress through need for recovery was statistically detectable, whereas a complementary indirect effect through recovery experiences was in the expected direction but did not meet the bootstrap criterion for statistical significance. Conclusion In this cross‐sectional sample, psychological capital was associated with lower perceived stress primarily through its association with reduced need for recovery rather than through a direct association with stress. Interventions intended to protect nurse well‐being should therefore be conceived as combining individual resource‐building with organizational architectures that enable effective recovery. Implication for Nursing Practice Psychological capital should be seen as one element in integrated interventions rather than a stand‐alone solution to nursing stress. Brief recovery‐focused interventions for nurses need to be combined with scheduling practices and organizational policies that protect rest and make recovery feasible, a configuration that appears more promising than psychological capital training alone. Reporting Method The study followed the STROBE Statement for the reporting of cross‐sectional studies. No Patient or Public Contribution This study focused on nurses as study participants. No patient or public stakeholder was involved in the design, conduct, or interpretation of the research, since the research question concerns occupational psychological resources rather than clinical practice or care delivery.